The diphthamide modification on elongation factor-2 renders mammalian cells resistant to ricin - Gupta, Pradeep K. (2008)
Diphthamide is a post-translational derivative of histidine in protein synthesis elongation factor-2 (eEF-2) that is present in all eukaryotes with no known normal physiological role. Five proteins Dph1-Dph5 are required for the biosynthesis of diphthamide. Chinese hamster ovary (CHO) cells mutated in the biosynthetic genes lack diphthamide and are resistant to bacterial toxins such as diphtheria toxin. We found that diphthamide-deficient cultured cells were 3-fold more sensitive than their parental cells towards ricin, a ribosome-inactivating protein (RIP). RIPs bind to ribosomes at the same site as eEF-2 and cleave the large ribosomal RNA, inhibiting translation and causing cell death. We hypothesized that one role of diphthamide may be to protect ribosomes, and therefore all eukaryotic life forms, from RIPs, which are widely distributed in nature. A protective role of diphthamide against ricin was further demonstrated by complementation where dph mutant CHO cells transfected with the corresponding DPH gene acquired increased resistance to ricin in comparison with the control transfected cells, and resembled the parental CHO cells in their response to the toxin. These data show that the presence of diphthamide in eEF-2 provides protection against ricin and suggest the hypothesis that diphthamide may have evolved to provide protection against RIPs.